Adulteration of bee honey : situational analysis in Costa Rica - Hernández Ching, Paola (2023)
The investigation covered the different actions that the country has taken to combat the adulteration of bee honey, using the quintuple helix innovation model: the measures implemented by different government organizations, the support provided by research centers to address this problem, the actions taken by the productive sector on their own, the role of consumers as direct stakeholders, and the environmental implications that a phenomenon like this can generate.